Karakterisasi Ganoderma spp. di Kabupaten Banyumas dan Uji Peran Basidiospora dalam Siklus Penyakit Busuk Batang - Nuniek Ina Ratnaningtyas; Siti Samiyarsih (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
Ganoderma sp., one of fungi belonged to the family Ganodermataceae, order of Aphyllophorales, class of Basidiomycetes is very widely spread.  This fungus is a soil-borne, and has parasitic and saprophytic features which are interesting because of their two contradictory roles namely harmful and beneficial effects.  As a plant parasite, Ganoderma is able to cause root and stem rot of tropical perennial crop plantation and forest which cause serious losses.  The fungus is well known as white rot fungus which is able to cause a wood rotten by lignin destruction.  On the contrary, the fungus has some advantages such as medical potentials.  In this study, some collections and characterization of Ganoderma spp. found in Banyumas has been conducted.  The technique used for sampling Ganoderma spp. mushroom is a survey with Purposive Random Sampling method.  Samples were taken from nature in the area of Banyumas Regency and its natural substrate were noted. Characterization based on the macromorphology and micromorphology was done for grouping and identification.  Micromorphology observations were done by slicing and painting samples with plants microtechnique method.  The result showed that there were 43 Ganoderma spp isolates, distributed from low to high lands of 100 - 500 m above sea level.  The most fungi were found on the high lands, in Baturraden sub district, which included 16 isolates.  The interesting finding is the discovery of Ganoderma spp. which attacked flamboyant plant (Delonix regia) in West Purwokerto sub district.  Based on micromorphology observations, these fungi form a basidium and basidiospore inside and below as well as the surface of the fruit body.  Some species were also found having such phenomenon so it needs further research on the role of basidiospora in the cycle of stem rot disease, especially basidiospora role in the initiation of diseases infection.  As the soil infecting mushroom, study of the disease spreading is focused more on the role of the mycelium found in the remaining plants as infecting the material.  Basidiopore role in the spread of the disease is rarely studied, but actually basidiospore is a potential source of genetic variation.